Declines in Lung Function After Antiretroviral Therapy Initiation in Adults With Human Immunodeficiency Virus and Tuberculosis: A Potential Manifestation of Respiratory Immune Reconstitution Inflammatory Syndrome. (25th September 2019) - Auld, Sara C; Maenetje, Pholo; Ravimohan, Shruthi; Weissman, Drew; Ncube, Itai; Mlotshwa, Mandla; Ratsela, Nelly; Chase, William; Vangu, Mboyo-Di-Tamba; Wallis, Robert; Churchyard, Gavin; Kornfeld, Hardy; et al.
Abstract: End-organ impairment has received relatively little research attention as a possible manifestation of tuberculosis immune reconstitution inflammatory syndrome (TB-IRIS). In this prospective cohort study, one-half of adults with human immunodeficiency virus and pulmonary tuberculosis experienced meaningful declines in lung function on antiretroviral therapy, suggesting a role for lung function in TB-IRIS definitions.